2000
DOI: 10.1074/jbc.m007907200
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Transcription Factor SAF Involves Its Phosphorylation by Protein Kinase C

Abstract: The transcription factor serum amyloid A (SAA)-activating factor (SAF), a family of zinc finger proteins, plays a significant role in the induced expression of the SAA gene. Activity of SAF is regulated by a phosphorylation event involving serine/threonine protein kinase (Ray, A., Schatten, H

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 31 publications
2
21
0
Order By: Relevance
“…The SAF family of transcription factors was initially identified as a regulator of serum amyloid A, an inflammation-responsive gene. The DNA binding activity of SAF-1 is normally detected in many tissues, but many inflammatory agents, including IL-1 and IL-6 alone or in combination (29), PMA (30), and bacterial lipopolysaccharide (25), are known to increase its DNA binding activity and overall transactivation potential. Phosphorylation of SAF-1 by protein kinase is critical for its action.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SAF family of transcription factors was initially identified as a regulator of serum amyloid A, an inflammation-responsive gene. The DNA binding activity of SAF-1 is normally detected in many tissues, but many inflammatory agents, including IL-1 and IL-6 alone or in combination (29), PMA (30), and bacterial lipopolysaccharide (25), are known to increase its DNA binding activity and overall transactivation potential. Phosphorylation of SAF-1 by protein kinase is critical for its action.…”
Section: Discussionmentioning
confidence: 99%
“…Cytokine-responsive induction of SAF-1 activity is mediated by the mitogen-activated protein kinase (MAPK) signaling pathway (31). The PMAmediated induction of SAF-1 involves its phosphorylation by protein kinase C␤ (30). Protein kinase A has also been shown to phosphorylate and activate SAF-1 (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…It is loosely associated with the mitochondrial membrane in normal cells, but integrates into mitochondrial membranes during induction of cell death. 47 Overexpression of BNIP3 results in a caspaseindependent cell death with features of necrosis, including opening of the permeability transition pore, and evidence of mitochondrial autophagy. 48 Hspin is a transmembrane protein that is localized primarily in the mitochondria.…”
Section: Inhibition Of Apoptosis Upstream Of the Mitochondria Preventmentioning
confidence: 99%
“…SAF-1 DNA-binding activity is normally detected in many tissues at a low level, but many inflammatory agents, including lipopolysaccharide (48), IL-1, IL-6 (45), and minimally modified low-density lipoprotein (46), are known to increase its DNA-binding activity and overall transactivating potential. In a recent study, we have shown that protein kinase C ␤ regulates phorbol 12-myristate 13-acetate-mediated activation of SAF-1 (39). As different inflammatory agents are known to activate different signaling pathways, it is likely that an additional protein kinase(s) is involved in the regulation of SAF activity in response to diverse inflammatory agents.…”
mentioning
confidence: 99%